2021
DOI: 10.1111/jfpp.15560
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of microwave cooking by two conventional cooking methods on the concentrations of polycyclic aromatic hydrocarbons and volatile N‐nitrosamines in beef cocktail smokies (smoked sausages)

Abstract: Volatile N‐nitrosamines (VNAs) and polycyclic aromatic hydrocarbons (PAHs) are two of the most hazardous compounds for human health in the meat products have cured by nitrite and smoke, on whose contents different cooking methods can have a significant effect on quality. The present study compared the effects of microwave as a novel cooking method and two conventional methods of pan‐frying and grilling on the VNAs and PAHs of beef cocktail smokies (smoked sausages, 55% meat). VNAs and PAHs were measured by Gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The relationship between cooking methods applied to meat products and cancer has been evaluated in several studies [ 89 , 90 ]. According to the literature, the effect of cooking methods on the level of these four contaminants in meat products varies [ 91 , 92 , 93 , 94 , 95 ]. In this study, the effect of the cooking method on the heat-treatment contaminant level in meat products was considered as deep/pan frying, grilling/barbecue, roasting, baking, and boiling, from the highest to the lowest.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between cooking methods applied to meat products and cancer has been evaluated in several studies [ 89 , 90 ]. According to the literature, the effect of cooking methods on the level of these four contaminants in meat products varies [ 91 , 92 , 93 , 94 , 95 ]. In this study, the effect of the cooking method on the heat-treatment contaminant level in meat products was considered as deep/pan frying, grilling/barbecue, roasting, baking, and boiling, from the highest to the lowest.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of quality, physical properties, protein denaturation, microstructure, and volatiles were investigated for microwave yak meat cooking. The findings indicated that cooking yak meat with a microwave resulted in better texture and volatile properties but greater cooking loss and decolorization compared to traditional boiling cooking [ 58 ]. In terms of health concerns, microwave cooking showed the lowest amount of total volatile N-nitrosamines and polycyclic aromatic hydrocarbons, which are two of the most hazardous compounds for human health, in beef cocktail smokies compared to pan-frying and grilling cooking [ 59 ].…”
Section: Meat Cooking Methodsmentioning
confidence: 99%
“…Other than the microbe's inactivation, microwave cooking can produce lower quantities of volatile nitrosamines than other cooking methods like grilling and pan‐frying (Mirzazadeh et al., 2021 ). The formation of carcinogenic nitrosamine in cured meat products is related to the high internal temperature during cooking and moisture content of the meat product.…”
Section: Minimal Processing Technologies As Nitrite Reduction Strategiesmentioning
confidence: 99%